Integrative Metagenomic Analyses Reveal Gut Microbiota-Derived Multiple Hits Connected to Development of Diabetes Mellitus - Sehad N. Alarifi; Essam Jamil Alyamani; Mohammed Alarawi; Azzam A. Alquait; Mohammed A. Alolayan; Ahmad M. Aldossary; Randa A. Abd EL-Rahman; Rashid Mir (Metabolites)
Background/Objectives: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder associated with gut dysbiosis. To investigate the association between gut microbiota and T2DM in a Saudi Arabian population. Methods: We conducted a comparative analysis of fecal microbiota from 35 individuals, including both T2DM patients and healthy controls. 16S rRNA gene sequencing was employed to characterize the microbial community structure. Results: Our findings revealed significant differences in microbial composition between the two groups. The T2DM group exhibited a higher abundance of Firmicutes and lower levels of Bacteroidetes compared to the healthy control group. At the genus level, T2DM patients showed a decrease in butyrate-producing bacteria such as Bacteroides and Akkermansia, while an increase in Ruminococcus and Prevotella was observed. Additionally, the T2DM group had a higher abundance of Faecalibacterium, Agathobacter, and Lachnospiraceae, along with a lower abundance of Bacteroides. Conclusions: These results suggest that alterations in gut microbiota composition may contribute to the development of T2DM in the Saudi Arabian population. Further large-scale studies are needed to validate these findings and explore potential therapeutic interventions targeting the gut microbiome.